2017
DOI: 10.2147/jpr.s139223
|View full text |Cite
|
Sign up to set email alerts
|

Ambroxol for the treatment of fibromyalgia: science or fiction?

Abstract: Fibromyalgia appears to present in subgroups with regard to biological pain induction, with primarily inflammatory, neuropathic/neurodegenerative, sympathetic, oxidative, nitrosative, or muscular factors and/or central sensitization. Recent research has also discussed glial activation or interrupted dopaminergic neurotransmission, as well as increased skin mast cells and mitochondrial dysfunction. Therapy is difficult, and the treatment options used so far mostly just have the potential to address only one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 298 publications
0
8
0
Order By: Relevance
“…Regarding safety, the clinical data for ambroxol for the treatment of pain seem favourable. In the studies reviewed here, no adverse skin effects or reactions were reported for topical ambroxol, 45–47,58 whereas oral formulations have so far been associated with a low incidence of minor side effects, including nausea, constipation, bowel/abdominal discomfort, heartburn, and dizziness. 41,61 Regarding its use in approved indications (ie, secretolytic therapy, respiratory distress syndrome, and pain relief in sore throat), the European Medicines Agency (EMA) published a revised safety assessment in 2015 which stated that, based on a small number of case reports, there is weak evidence of a possible risk of hypersensitivity and skin reactions.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Regarding safety, the clinical data for ambroxol for the treatment of pain seem favourable. In the studies reviewed here, no adverse skin effects or reactions were reported for topical ambroxol, 45–47,58 whereas oral formulations have so far been associated with a low incidence of minor side effects, including nausea, constipation, bowel/abdominal discomfort, heartburn, and dizziness. 41,61 Regarding its use in approved indications (ie, secretolytic therapy, respiratory distress syndrome, and pain relief in sore throat), the European Medicines Agency (EMA) published a revised safety assessment in 2015 which stated that, based on a small number of case reports, there is weak evidence of a possible risk of hypersensitivity and skin reactions.…”
Section: Discussionmentioning
confidence: 77%
“…80 There is also increasing evidence for involvement of inflammatory factors, oxidative stress, and neurodegenerative changes. 45 The overlap between fibromyalgia-proposed pathophysiological components and multiple mechanisms of action of ambroxol has been thoroughly discussed by Kern and Schwickert. 45 In 2017, the results of an open-label pilot study of oral ambroxol treatment (30 mg 3 times a day for 1 month) as an add-on to stable pharmacological therapy were published.…”
Section: Fibromyalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…It might also be associated with the central sensitization phenomenon that amplifies neuronal activation in pain‐processing regions in patients with chronic pain, and can provoke long‐term changes in brain functioning (Woolf, ). Ambroxol potentially reversed central pain sensitization during initial treatment (Kern & Schwickert, ). This effect might be associated with Nav1.8 channels and/or the scavenging activity of free radicals (Jang, Song, Shin, Han, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…The intrathecal administration also showed an anti‐allodynic effect . Reductions of allodynia and hyperalgesia by topical ambroxol in humans so far have been reported in case series for neuropathic pain, nociceptive pain, mixed pain situations, and even topical and oral, given for hypersensitivities in fibromyalgia . For the patients described in this article, however, an alleviation of allodynic symptoms thus could be explained.…”
Section: Discussionmentioning
confidence: 99%